Restating Copyright Law’s Originality Requirement - Hughes, Justin (The Columbia Journal of Law & the Arts, 2021)
In 2015, the American Law Institute (ALI) launched a project to create a Restatement of the Law, Copyright. Concern, objection, and disagreement about the ALI’s Restatement projects is not new, but the Restatement of Copyright project seems to be particularly controversial among industries dependent on copyright protection. The drafting group has now worked through several versions of some proposed sections; a handful of these have been approved by the ALI Council and are ready to go before the ALI general membership. So now is a good time for close analysis of the chunks of the projects that have crystallized. This Article reviews the 2020 draft Restatement’s presentation of American copyright law’s threshold requirement for protection: that copyright protects only “original works of authorship,” and how that “originality” requirement should be understood in light of the Supreme Court’s 1991 decision in Feist v. Rural Telephone. Copyright’s originality requirement is a challenging subject for a Restatement because what is unquestionably agreed is that black letter law is limited, formulaic, and opaque. Not surprisingly, the Restatement’s handling of this topic hews close to the words of the Supreme Court’s modern pronouncement on the issue, sometimes to the detriment of a richer, potentially more enlightening discussion. The discussion here is based principally on “Tentative Draft No. 1” of the Restatement, released on April 8, 2020,3 but the discussion will also include consideration of the earlier “Council Drafts”4 that led to the 2020 proposal. Part I of the Article briefly describes the controversial beginnings of this Restatement project—and, as of 2021, the continuing animosity of copyright stakeholders to the project. Part II lays out the 2020 draft Restatement’s core provisions on copyright originality, the modest evolution of these provisions since the 2017 draft, and some concerns with what these sections, Comments, and Reporters’ Notes say. In broad strokes, the draft Restatement’s take on copyright originality is faithful to the Supreme Court’s 1991 Feist v. Rural Telephone decision, perhaps too much so. Part II.A explores the draft Restatement’s presentation of Feist’s “modicum of creativity” requirement, raising some issues both with what the Reporters have said so far and equally with what the draft Restatement seems unwilling to say about minimal creativity. Part II.B discusses the draft Restatement’s presentation of Feist’s “independent creation” requirement; here the concern is that the draft may conflate independent creation with minimal creativity in a way that does not contribute to coherence in copyright law.